Integrating multi-omics and experimental techniques to decode ubiquitinated protein modifications in hepatocellular carcinoma - Yang, Haikun; Chen, Yuan; Zhou, Zheng; Wang, Yanjing; Li, Peng; Li, Yang (Frontiers in Pharmacology, 2025)
BackgroundUbiquitination, a critical post-translational modification, plays a pivotal role in regulating protein stability and activity, influencing various aspects of cancer development, including metabolic reprogramming, immune evasion, and tumor progression. However, the specific role of ubiquitination in hepatocellular carcinoma (HCC), particularly in relation to the tumor microenvironment (TME), remains poorly understood. This study aims to systematically explore the role of ubiquitination in shaping the TME of HCC, with a focus on its impact on cancer progression and immune modulation.MethodsWe performed bioinformatics analysis by integrating multiple publicly available HCC datasets to assess the ubiquitination status across various cell types in the TME, including plasma cells, fibroblasts, endothelial cells, and epithelial-mesenchymal transition (EMT) cells. Ubiquitination scores were calculated to categorize these cell types, and survival data, along with spatial transcriptomics, were employed to evaluate how different levels of ubiquitination influence HCC progression. In vitro experiments, such as transwell, CCK8, and wound healing assays, were used to further investigate the role of the key ubiquitination gene UBE2C in HCC phenotypes.ResultsOur study revealed that ubiquitination-related genes are significantly upregulated in HCC tissues, with high expression levels correlating with poor prognosis in patients. Pathway analysis showed that these genes are enriched in key processes such as cell cycle regulation, DNA repair, metabolic reprogramming, and p53 signaling. These pathways contribute to the TME by promoting tumor cell proliferation, facilitating matrix remodeling, and enhancing angiogenesis. Notably, UBE2C, a critical ubiquitination enzyme, appears to play a key role in immune evasion, potentially by inhibiting anti-tumor immune responses and reducing the immune system’s ability to recognize and eliminate tumor cells. Furthermore, experimental data confirmed that UBE2C overexpression promotes HCC cell proliferation, invasion, and metastasis, further supporting its role in tumor progression and TME remodeling.ConclusionThis study reveals the multifaceted regulatory roles of ubiquitination in HCC. Ubiquitination not only supports proliferation and anti-apoptotic functions within tumor cells but also promotes tumor progression by modulating the activity of immune and stromal cells. Among all ubiquitination-related genes, UBE2C emerges as a potential prognostic biomarker and therapeutic target in HCC, offering new directions for precision treatment of HCC in the future.